Away in a manger [compact disc, unabridged] - Bowen, Rhys (Bowen, Rhys. Molly Murphy mysteries., 2015)
It's Christmastime in 1905 New York City, and for once, Molly Murphy Sullivan is looking forward to the approaching holidays. She and Daniel have a baby son and 12-year-old Bridie is living with them as their ward. As Molly and the children listen to carolers in the street, they hear a lovely little voice and see a beggar girl, huddled in a doorway singing Away in a Manger. Bridie is touched by the girl's ragged clothes and wants to help her out if they can. They give her a quarter, only to watch a bigger boy take it from her. But it turns out he is the girl's brother, and they've come from England and are living with an aunt who mistreats them terribly. When the young boy is accused of stealing a purse, Molly intervenes on his behalf.